Longitudinal Comparison of the Microbiota During Klebsiella pneumoniae Carbapenemase-Producing Klebsiella pneumoniae (KPC-Kp) Acquisition in Long-Term Acute Care Hospital (LTACH) patients. (4th October 2017) - Seekatz, Anna; Bassis, Christine M; Lolans, Karen; Yelin, Rachel D; Moore, Nicholas M; Okamoto, Koh; Rhee, Yoona; Bell, Pamela; Dangana, Thelma; Sidimirova, Galina; Weinstein, Robert A; Fogg, Louis; et al.
Abstract: Background: Colonization with KPC-Kp precedes infection and represents a potential target for intervention. To identify microbial signatures associated with KPC-Kp acquisition, we conducted a prospective, longitudinal study of the fecal microbiota in LTACH patients at risk of acquiring KPC-Kp. Methods: We collected admission and weekly rectal swab samples from patients admitted to one LTACH from May 2015 to May 2016. Patients were screened for KPC-Kp by PCR at each sampling time. KPC acquisition was confirmed by culture of KPC-Kp. To assess changes in the microbiota related to acquisition, we sequenced the 16S rRNA gene (V4 region) from collected rectal swabs. Diversity, intra-individual changes, and the relative abundance of the operational taxonomic unit (OTU) that contains KPC-Kp were compared in patients who were KPC-Kp negative upon admission and who had at least one additional swab sample collected. Results: 318 patients (1247 samples) were eligible for analysis; 3.7 samples (mean) were collected per patient. Sixty-two patients (19.5%) acquired KPC-Kp (cases) and 256 patients remained negative for all carbapenem-resistant Enterobacteriaceae throughout their stay (controls). Median length of stay before KPC-Kp detection was 14.5 days. At time of KPC-Kp acquisition, levels of an Enterobacteriaceae OTU increased significantly compared with pre-acquisition samples and to samples from control patients (Wilcoxon test, P  < 0.0001). Similarly, we observed a decrease in total diversity of the fecal microbiota at time of acquisition in cases ( P  < 0.01). Compared with controls, cases exhibited decreased intra-individual fecal microbiota similarity immediately prior to acquisition of KPC-Kp ( P  < 0.01). Comparison of microbial features at time of admission using random forest revealed a higher abundance of Enterococcus and Escherichia OTUs in controls vs cases. Conclusion: We observed intra-individual changes in the fecal microbiota of case patients prior to acquisition of KPC-Kp. Compared with patients who did not acquire KPC-Kp, cases exhibited significant changes in microbiota diversity and increased abundance of potential KPC-Kp at acquisition. Our results suggest that shifts in the microbiota may precede colonization by KPC-Kp. Disclosures: N. M. Moore, Cepheid: Research Contractor, Funded and provided reagents for associated research projects; R. A. Weinstein, OpGen: Receipt of donated laboratory services for project, Research support; CLorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Molnlycke: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; M. Y. Lin, Sage, Inc.: receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; OpGen, Inc.: receipt of in-kind laboratory services, Conducting studies in healthcare facilities that are receiving contributed product; M. K. Hayden, OpGen, Inc.: Receipt of donated laboratory services for project, Research support; Clorox: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Molnlycke: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product; Sage Products: Receipt of contributed product, Conducting studies in healthcare facilities that are receiving contributed product.